Patient perceptions of transvaginal ultrasound in the diagnosis and management of infertility: a cross-sectional study - Babita,; Dev, Kapil (International Journal Of Community Medicine And Public Health, 2024)
Background: Infertility is a significant global health concern, affecting a substantial percentage of couples. Transvaginal ultrasound (TVUS) has emerged as a key diagnostic tool in the evaluation along with treatment of infertility, offering improved imaging quality for the assessment of reproductive health conditions. This study aimed to gauge patient perceptions of the effectiveness, comfort, and role of TVUS in infertility diagnosis and treatment planning. Methods: A cross-sectional study was conducted across 200 women undergoing infertility evaluation at a reproductive health clinic. Data was collected utilising a structured questionnaire that included demographic information, clinical history, and patient perceptions of TVUS. Variables such as effectiveness, comfort during the procedure, and the role of TVUS in treatment planning were analyzed. Descriptive statistics were utilised to encapsulate the data, and results were offered as frequencies along with percentages. Results: The majority of participants (72.0%) were aged 25-34 years, with 58.4% being married and 64.8% having a college education. Most participants (62.0%) had experienced infertility for 1-5 years, and 46.0% had a previous diagnosis of reproductive health conditions. A large portion of participants (38.5%) strongly agreed that TVUS was effective in providing diagnostic insights, and 45.5% agreed that they felt comfortable during the procedure. Additionally, 48.5% agreed that TVUS played a crucial role in their treatment planning. Conclusions: Transvaginal ultrasound is perceived as an effective and valuable tool in the diagnosis along with management of infertility. While most patients reported comfort with the procedure, there remains a need to address the experiences of those who expressed discomfort. The conclusions highlight the importance of TVUS in shaping treatment strategies and enhancing patient outcomes in infertility care.